(untitled) (Revista Escenarios Sociojurídicos, 2023)
Abstract Colombian constitutional history is one of the most forgotten and devalued issues today, over the years we find constitutional gaps in the different eras of what was an extensive process to advance as a country in Constitutional law. It is vitally important that the Colombian people know their history, their constitutional process, the change of thought and ideologies over the years and their transitory struggle to become a free and independent nation. This article was made with the intention of exposing an important part of the valuable and precious Colombian history regarding the constitutionalist process, with the purpose of capturing various characteristic events that happened in 1819 inside and outside the congress of narrowness, reflect those discussions that were held in order to resolve what would be the appropriate Political System to govern in the nascent Republic of Colombia, resolving between centralism and federalism, whose decision together with the creation of the constitution of Cucuta of 1821 specified the constitutionalist course to follow and thus marked the Colombian constitutional history.